PERAN PEGAWAI PENCATAT PERKAWINAN UNTUK MENCEGAH PEMBATALAN PERKAWINAN TERHADAP PEMALSUAN IDENTITAS - Alisya Rahma Saebani, (2023)
Marriage can be said to be valid if it fulfills the conditions and pillars of marriage. Marriages that have taken place are filed for annulment if it turns out that the conditions for the marriage have not been met. Marriage is invalid if there is a violation committed by the prospective bridegroom, a violation of the prohibition on marriage, or if it does not fulfill the pillars and conditions of marriage. The formulation of the research problem is: (1) What are the judges' considerations in deciding a marriage annulment case due to identity falsification in Case Decision Number 3400/Pdt.G/2021/PA.Bks? (2) What should the role of the marriage registrar be in verifying the identities of the parties in order to avoid marriage annulment? This research is normative juridical research with secondary data, a statutory approach, and a case approach. According to Article 22 of Law No. 1 of 1974 Concerning Marriage, a marriage can be canceled if the parties do not meet the requirements to enter into a marriage, and a marriage can be canceled if there is a misunderstanding about the husband or wife (Article 27 Paragraph 2 of Law No. 1 of 1974 Concerning Marriage). In marriage, the role of marriage registrar is needed to examine and oversee the assigned marriage requirements so that errors regarding the administration of the marriage do not occur and prevent the marriage from being cancelled. If there is an intentional or unintentional mistake made by the Marriage Registrar, they will be subject to sanctions in accordance with Article 45, paragraph 1, letter b, of Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage, with a sentence of imprisonment for a maximum of three (3) years. 3 months or a maximum fine of Rp. 7,500.00 (seven thousand five hundred rupiah). Keywords: Marriage Annulment, Identity Forgery, Marriage Registrar